2015
DOI: 10.1179/1477570015z.00000000095
|View full text |Cite
|
Sign up to set email alerts
|

Straddling Boundaries: Culture and the Canada-US Border

Abstract: On Monday March 16th 2015, Canadian Public Safety Minister Steven Blaney and US Homeland Security Secretary Jeh Johnson signed an agreement that will pave the way for the long-awaited expansion of pre-clearance customs procedures at the Canada-US border, the latest in a series of proposals designed to protect domestic security, preserve international trade, and maintain strong diplomatic relations between Canada and the US in the wake of 9/11. Presented under the general banner of Beyond the Border, an initiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The border narrative helps to deconstruct the binary opposition that is created by the borders. David Stirrup and Jan Clarke (2015) assert that "Border studies of course long has demonstrated the ways in which cultural representation and production can effect, at least metaphorically, the deconstruction of binary structures implied by a border" (2). King expresses Native's concerns about racial discrimination and stereotype.…”
mentioning
confidence: 99%
“…The border narrative helps to deconstruct the binary opposition that is created by the borders. David Stirrup and Jan Clarke (2015) assert that "Border studies of course long has demonstrated the ways in which cultural representation and production can effect, at least metaphorically, the deconstruction of binary structures implied by a border" (2). King expresses Native's concerns about racial discrimination and stereotype.…”
mentioning
confidence: 99%